Answer: The solutions are
(0, - 6)
(7, 8)
Explanation:
The given system of equations is expressed as
y = x² - 5x - 6- - - - - - - - - - - - 1
y = 2x - 6- - - - - - - - - - - 2
We would apply the method of substitution by substituting equation 2 into equation 1. It becomes
x² - 5x - 6 = 2x - 6
x² - 5x - 6 = 2x - 6
x² - 5x - 2x - 6 + 6 = 0
x² - 7x = 0
x(x - 7) = 0
x = 0 or x - 7 = 0
x = 7 or x = 0
Substituting x = 0 into equation 2, it becomes
y = 2 × 0 - 6
y = - 6
Substituting x = 7 into equation 2, it becomes
y = 2 × 7 - 6
y = 14 - 6
y = 8